Building Site–Level Capacity for Functional Assessment-Based Interventions: Outcomes of a Professional Learning Series. (November 2022) - Common, Eric Alan; Lane, Kathleen Lynne; Oakes, Wendy Peia; Schellman, Liane E.; Shogren, Karrie; Germer, Kathryn A.; Quell, Ashley E.; Lane, Nathan Allen
In this replication and extension study, we examined the effects of educators' participation in practice-based professional learning (PBPL) to design, implement, and evaluate functional assessment-based interventions (FABIs). We randomly assigned school-site teams ( k = 69; N = 342) to cohorts trained by either university or state technical assistance providers. In a randomized cluster design, we replicated and extended previous research by examining procedural integrity, participant learning outcomes, completion and quality levels of PBPL-FABI activities, and student outcomes. Results provide (a) additional evidence to support PBPL-FABI in improving school-site teams' knowledge, confidence, and use and (b) initial evidence for its scalability, as evidenced by state technical assistance providers' high implementation levels comparable with university trainers. We conclude with a discussion regarding PBPL-FABI and considerations for future research.